Town born : the political economy of New England from its founding to the Revolution - Levy, Barry (Early American studies., 2009)
In Town Born, Barry Levy shows that New England's distinctive and far more egalitarian order was due neither to the colonists' peasant traditionalism nor to the region's inhospitable environment. Instead, New England's labor system and relative equality were every bit a consequence of its innovative system of governance, which placed nearly all land under the control of several hundred self-governing town meetings. As Levy shows, these town meetings were not simply sites of empty democratic rituals but were used to organize, force, and reconcile laborers, families, and entrepreneurs into profitable export economies. The town meetings protected the value of local labor by persistently excluding outsiders and privileging the town born.--From publisher description.